SELF ACCEPTANCE OF THE MAIN CHARACTER IN MATT HAIG'S MIDNIGHT LIBRARY - Putri, Mutiara; Widisanti, Ni Made; Ratih P, Shita Dewi (Universitas Pakuan, 2023)
This study is an analysis of the main character with the aim of showing how the main character responds and describes the problem of self-acceptance that affects her mental health.The analytical method used in this study is a qualitative descriptive analysis method along with the psychoanalytic theory proposed by Sigmund Freud with the study of developmental psychology. The results of the research show that the level of self-acceptance can affect a person's life. The way the main character responds and describes self-acceptance is by looking back at her past life and embracing it in order to accept herself more as she is so she can move on and live a better life.Keywords: Midnight Library, mental health, self-acceptance and life.